2019
DOI: 10.1007/s13595-019-0816-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability of stone pine (Pinus pinea L.) fruit traits impacting pine nut yield

Abstract: & Key message Cone to pine nut yield (PY), an important commercial feature of stone pine cropping, was higher in Chile than in main producer countries. PY is highly variable along years and depends on pine nut number inside cones, followed by pine nut weight. Cone morphometry is not a good indicator of PY, thus selecting cones for size/weight will not improve it. & Context Stone pine nuts are highly appreciated; however, pine nut yield (total pine nut weight as percentage of cone weight), important feature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
3
14
0
1
Order By: Relevance
“…The average SD and SL determined by Loewe-Muñoz et al (2018) were 1 and 2 cm, respectively, while in the present study, they were 0.9 and 1.8 cm, respectively; these latter measurements are similar to those reported by Ganatsas et al (2008) and Carcel et al (2012). Loewe-Muñoz et al (2019) report that the mean 6year measurement of SN in plantations in Chile was 113 which is more than double that found in the present study (50), with the Çanakkale-Kirazlı population having the lowest (25). A positive correlation was found between SN and CW; this finding supports several previous studies that have indicated that heavier cones contain more seeds Boutheina et al 2013;Loewe-Muñoz et al 2019).…”
Section: Seed Traitssupporting
confidence: 89%
See 4 more Smart Citations
“…The average SD and SL determined by Loewe-Muñoz et al (2018) were 1 and 2 cm, respectively, while in the present study, they were 0.9 and 1.8 cm, respectively; these latter measurements are similar to those reported by Ganatsas et al (2008) and Carcel et al (2012). Loewe-Muñoz et al (2019) report that the mean 6year measurement of SN in plantations in Chile was 113 which is more than double that found in the present study (50), with the Çanakkale-Kirazlı population having the lowest (25). A positive correlation was found between SN and CW; this finding supports several previous studies that have indicated that heavier cones contain more seeds Boutheina et al 2013;Loewe-Muñoz et al 2019).…”
Section: Seed Traitssupporting
confidence: 89%
“…Loewe-Muñoz et al (2019) report that the mean 6year measurement of SN in plantations in Chile was 113 which is more than double that found in the present study (50), with the Çanakkale-Kirazlı population having the lowest (25). A positive correlation was found between SN and CW; this finding supports several previous studies that have indicated that heavier cones contain more seeds Boutheina et al 2013;Loewe-Muñoz et al 2019). In our findings, the average cone to seed yield (SY) ranged between 8.1 and 18.5%, while Loewe-Muñoz et al 2019reported 6-year-mean values ranging from 17.7 to 22.6%.…”
Section: Seed Traitssupporting
confidence: 43%
See 3 more Smart Citations